TEHORIES OF CONNECTIONS - PRACTICAL IMPLICATIONS IN ACQUIRING MOTOR SKILLS - Zoran Milošević; Nebojša Maksimović; Nada Milošević; Borislav Obradović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Theories of learning which are classified in two broad schools as theories of connections and cognitive theories, differ among themselves according to specific interaction relationships between external stimulus (S), reaction and behavior and organism (R), i.e. particular learner (O). In relation to pedagogical practices, predominance of a certain school is not rare, often without any objective insight into their potentials related to age, sex, learning contents and other determinants. Well-known approaches within the theories of relations include classical Pavlov reflex, Guthry's close conditioning, associating of Thorndyke, and Skinner's efficient conditioning. Practical implications of these theories in acquiring motor skills are related to an active learner's approach, significance of repetition - exercising, supporting, and rewarding correct answers, as well as strengthening a new behavior by imitation of a sample - modeling.